Urinary V‐Set Ig Domain‐Containing Protein 4 and Immune Complexes for Tracking Lupus Nephritis and Renal Pathology - Aygun Teymur; Chenling Tang; Fariz Nazir; Neda Ostadnejad; Qi Cai; Ramesh Saxena; Tianfu Wu (ACR Open Rheumatology)
Objective This study aims to investigate whether V‐set Ig domain‐containing protein 4 (VSIG4; also known as complement receptor of the Ig superfamily [CRIg]) forms immune complexes (ICxs) with IgG and complement component 3 (C3) in the kidneys of patients with lupus nephritis (LN) and to assess the potential of urinary VSIG4 and VSIG4‐ICx as noninvasive biomarkers of LN. Methods Immunofluorescent staining was employed to detect the deposition of VSIG4 (CRIg), IgG, and C3 in kidney tissue. Urine samples from 102 patients with LN, 51 healthy controls (HCs), and 13 patients with chronic kidney disease (CKD) were analyzed via enzyme‐linked immunosorbent assay for VSIG4‐ICx and free‐form VSIG4. Results Immunofluorescence costaining demonstrated the colocalization of VSIG4, IgG, and C3 in the kidneys of those with LN and elevated VSIG4 protein expression in the glomeruli regions in LN. Compared with HCs and those with CKD, patients with LN exhibited significantly elevated levels of urinary VSIG4 in both free form and ICx. Urinary VSIG4‐ICx correlated with clinical parameters, including the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) (R = 0.55, P < 0.0001), renal SLEDAI (R = 0.52, P < 0.0001), estimated glomerular filtration rate (−0.5, P < 0.001), activity index (R = 0.25, P < 0.05), chronicity index (R = 0.32, P < 0.05), complement C3 (R = −0.33, P < 0.05), and complement C4 (R = −0.31, P < 0.05). The strong association of the urinary VSIG4‐ICx with disease activity metrics and histopathologic evidence underscores its potential for clinical utility in diagnosing and monitoring LN. Conclusion VSIG4‐ICx shows promise as a novel urine biomarker for LN, with potential utility for diagnosis and disease monitoring.